Inventarisasi Jenis Tumbuhan Invasif Pada Area Terbuka Serta Pemanfaatannya di Kampus II UIN Sunan Gunung Djati Bandung - Aida Syakira Khoerunnisa; Syifa Azkia Azharia; Rahmat Taufik Mustahiq Akbar (International Forum of Researchers and Lecturers, 2024)
The growth of invasive foreign plants can change the structure and composition of species in the ecosystem, where the growth of native plant species will be unable to compete with invasive foreign plants which will then slowly experience extinction. Invasive alien plants have detrimental impacts on the environment and economy. The open area on campus 2 of UIN Sunan Gunung Djati Bandung is an area that is currently overgrown with various types and types of plants, where apart from plants planted deliberately, there are also invasive plants growing around it. The invasion process does not occur simultaneously or all at once, but rather gradually and begins with the presence of invasive species in an area of ​​land, which then takes over the new habitat or territory. Invasive plants will become more dominant in their growing area with fast growth characteristics and large and densely developed roots. This research aims to identify types of invasive foreign plants, their distribution factors, and the use of invasive plants found in open areas on campus 2 of UIN Sunan Gunung Djati Bandung. The method used in this research is the exploration method combined with the inventory method by observing and taking pictures and then identifying using literature sources. The result was that there were 27 plant species, of which 12 were included in the invasive plant species in Indonesia and the dominant family was the Asteraceae family. Apart from that, this research also examined the use of invasive plants from various literature, one of the plant species studied was Putri Malu (Mimosa pudica L..) has been used as a traditional medicine in healing burns.